Effect of volume expansion with hypertonic- and isotonic saline and isotonic glucose on sodium and water transport in the principal cells in the kidney - Jensen, Janni M; Mose, Frank H; Bech, Jesper N; Nielsen, Soren; Pedersen, Erling B (BMC nephrology, 2013)
The renal distal nephron plays an important role in the maintenance of sodium balance, extra cellular volume and blood pressure. The degree of water transport, via aquaporin2 water channels (AQP2), and sodium transport, via epithelial sodium channels (ENaC) in renal collecting duct principal cells are reflected by the level of urinary excretion of AQP2 (u-AQP2) and the γ-fraction of ENaC (u-ENaCγ). The effects of an acute intravenous volume load with isotonic saline, hypertonic saline and glucose on u-AQP2, u-ENaCγ and underlying mechanisms have never been studied in a randomized, placebo-controlled trial in healthy humans. We studied the effects of 0.9% saline (23 ml/kg), 3% saline (7 ml/kg) and 5% glucose (23 ml/kg) on u-AQP2 and u-ENaCγ, fractional sodium excretion (FENa), free water clearance (CH2O), and plasma concentrations of vasopressin (AVP), renin (PRC), angiotensin II (ANG II) and aldosterone (Aldo) in a randomized, crossover study of 23 healthy subjects, who consumed a standardized diet, regarding calories, sodium and fluid for 4 days before each examination day. After isotonic saline infusion, u-AQP2 increased (27%). CH2O and u-ENaCγ were unchanged, whereas FENa increased (123%). After hypertonic saline infusion, there was an increase in u-AQP2 (25%), u-ENaCγ (19%) and FENa (96%), whereas CH2O decreased (-153%). After isotonic glucose infusion, there was a decrease in u-AQP2 (-16%), ENaCγ (-10%) and FENa (-44%) whereas CH2O increased (164%). AVP remained unchanged after isotonic saline and glucose, but increased after hypertonic saline (139%). PRC, AngII and p-Aldo decreased after isotonic and hypertonic saline infusion, but not after glucose infusion. Volume expansion with 3% and 0.9% saline increased u-AQP2, while isotonic glucose decreased u-AQP2. Infusion of hypertonic saline increased u-ENaCγ, whereas u-ENaCγ was not significantly changed after isotonic saline and tended to decrease after glucose. Thus, the transport of water and sodium is changed both via the aquaporin 2 water channels and the epithelial sodium channels during all three types of volume expansion to regulate and maintain water- and sodium homeostasis in the body. Clinical Trial no: NCT01414088.